BIOMARKERS IN OBESITY-RELATED METABOLIC SYNDROME: FROM PATHOPHYSIOLOGY TO CLINICAL APPLICATION - Kostovska, Irena; Tosheska Trajkovska, Katerina (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Obesity-related metabolic syndrome (MetS) represents a complex, multifactorial disorder characterized by central obesity, insulin resistance, dyslipidemia, hypertension, and chronic low-grade inflammation. Its rising global prevalence underscores the urgent need for comprehensive understanding and early detection strategies. While traditional clinical and biochemical parameters provide insight into overt metabolic dysfunction, they often fail to capture upstream molecular disturbances. Recent research has identified a spectrum of novel biomarkers that reflect the pathophysiological mechanisms underlying MetS, including inflammatory mediators (high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor-alpha, monocyte chemoattractant protein-1, plasminogen activator inhibitor-1), adipokines and hormonal regulators (adiponectin, leptin, resistin, visfatin, ghrelin, glucagon-like peptide-1), oxidative stress and endothelial dysfunction markers (malondialdehyde, 8-isoprostane, oxidized LDL, asymmetric dimethylarginine, paraoxonase-1), thyroid function indicators (TSH, free thyroxine, anti-thyroid peroxidase antibodies), vitamin D, and genetic/epigenetic modulators (microRNAs and DNA methylation patterns). This review summarizes current evidence on these biomarkers, highlighting their roles in elucidating disease mechanisms, enabling early risk assessment, guiding therapeutic interventions, and supporting precision medicine approaches. Future research directions are proposed to standardize assays, validate findings across diverse populations, and develop integrated multi-marker panels to optimize the management of obesity-related MetS. Key words: Obesity, Metabolic syndrome, Adipokines, Inflammation, Insulin resistance,